Promoting Agricultural Growth in Rwanda : Recent Performance, Challenges and Opportunities - World Bank (Washington, DC, 2014)
Rwanda is experiencing its best growth performance since independence. With average annual GDP growth rate of 8 percent and 5.2 percent for agricultural GDP from 1999-2012, Rwanda s recent growth is a historical record. The poverty headcount fell from 59 percent in 2001 to 45 percent in 2011, and agriculture continues to be one of the main drivers of growth and poverty reduction in Rwanda, significantly lifting rural households out of poverty. Yet, challenges in the agriculture sector remain. Specifically, to: (i) sustain the productivity gains in the short and medium-term, which have contributed to strong agriculture growth and raised rural incomes; ii) increase and improve nutrition security for the rural population; iii) strengthen and deepen value chain development including increasing agro-processing to create non-farm employment; iv) secure and strengthen linkages to domestic and international markets for agriculture production; and v) enhance the enabling environment to attract the private sector to invest in the sector and add value to the productivity increases.